The Charcoal Vision: A Win–Win–Win Scenario for Simultaneously Producing Bioenergy, Permanently Sequestering Carbon, while Improving Soil and Water Quality - Laird, David A. (Agronomy journal, 2008)
Processing biomass through a distributed network of fast pyrolyzers may be a sustainable platform for producing energy from biomass. Fast pyrolyzers thermally transform biomass into bio‐oil, syngas, and charcoal. The syngas could provide the energy needs of the pyrolyzer. Bio‐oil is an energy raw material (∼17 MJ kg−1) that can be burned to generate heat or shipped to a refinery for processing into transportation fuels. Charcoal could also be used to generate energy; however, application of the charcoal co‐product to soils may be key to sustainability. Application of charcoal to soils is hypothesized to increase bioavailable water, build soil organic matter, enhance nutrient cycling, lower bulk density, act as a liming agent, and reduce leaching of pesticides and nutrients to surface and ground water. The half‐life of C in soil charcoal is in excess of 1000 yr. Hence, soil‐applied charcoal will make both a lasting contribution to soil quality and C in the charcoal will be removed from the atmosphere and sequestered for millennia. Assuming the United States can annually produce 1.1 × 109 Mg of biomass from harvestable forest and crop lands, national implementation of The Charcoal Vision would generate enough bio‐oil to displace 1.91 billion barrels of fossil fuel oil per year or about 25% of the current U.S. annual oil consumption. The combined C credit for fossil fuel displacement and permanent sequestration, 363 Tg per year, is 10% of the average annual U.S. emissions of CO2–C.